Another kind of justice : Canadian military law from confederation to Somalia - Madsen, Chris, 1968- (CEL - Canadian Publishers Collection., 1999)
"Another Kind of Justice is the first historical survey of Canadian military law, providing valuable insights into military justice in Canada, the purpose of military law, and the level of legal professionalism within the Canadian military."--Jacket